2014
DOI: 10.5586/asbp.2001.027
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose degradation in sink and source poplar leaves treated with sulfite

Abstract: Sulfite at concentrations from 0.5 to 5.0 mM was supplied to illuminated, detached poplar (Populus deltoides Bartr. ex Marsh) leaves via the transpiration stream. Concentrations of chlorophyll a and b, carotenoids, glucose, fructose, sucrose and starch, and extractable specific activities of sucrose synthase (SuSy), acid invertase (AI) and neutral invertase (NI) were measured. In sink and source leaves chlorophylls and carotenoids appeared to be increased by sulfite at concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The enzyme degrading the sucrose in SDAs could be invertase due to its high stability against SO 2 and the suitable pH of the samples for this enzyme . Similarly, Lorenc‐Plucinska et al . reported that total sucrolytic activities (acidic invertase activity + neutral invertase activity + sucrose synthase activity) in poplar leaves increased by increasing SO 2 concentration.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The enzyme degrading the sucrose in SDAs could be invertase due to its high stability against SO 2 and the suitable pH of the samples for this enzyme . Similarly, Lorenc‐Plucinska et al . reported that total sucrolytic activities (acidic invertase activity + neutral invertase activity + sucrose synthase activity) in poplar leaves increased by increasing SO 2 concentration.…”
Section: Resultsmentioning
confidence: 98%
“…Before storage, the SO 2 concentrations of the samples were 451, 832, 1594, 2112 and 3241 mg kg −1 ( Table 1). To reach the targeted SO 2 concentrations, except for 3241 mg kg −1 , the same amount of apricots (125 kg) was exposed to the same amount of SO 2 gas (300 g) for different times (30,45,180 and 360 min, respectively). However, when 300 g SO 2 gas was used, the SO 2 concentration of the apricots could not have reached approximately 3000 mg kg −1 , which represents the SO 2 concentration in SDAs stored for at least 1 year in Malatya.…”
Section: So 2 Absorption Kinetics Of Dried Apricots and Changes In Somentioning
confidence: 99%